2011
DOI: 10.1523/jneurosci.6194-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Alterations to the Nigrostriatal System in Mice Lacking All Three Members of the Synuclein Family

Abstract: The synucleins (α, β and γ) are highly homologous proteins thought to play a role in regulating neurotransmission and are found abundantly in presynaptic terminals. To overcome functional overlap between synuclein proteins and to understand their role in presynaptic signalling from mesostriatal dopaminergic neurons, we produced mice lacking all three members of the synuclein family. The effect on the mesostriatal system was assessed in adult (4-14 month old) animals using a combination of behavioural, biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 50 publications
16
167
0
2
Order By: Relevance
“…These data are consistent with previous studies showing that the synuclein family of proteins are likely to play a role both in normal physiological neurotransmitter release (11,12,19,20) and in the regulation of transporter function (21,22). In vitro studies have shown that overexpression of α-synuclein inhibits the release of catecholamines from adrenal chromaffin and PC12 cells, probably owing to a reduced pool of readily releasable vesicles (9).…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with previous studies showing that the synuclein family of proteins are likely to play a role both in normal physiological neurotransmitter release (11,12,19,20) and in the regulation of transporter function (21,22). In vitro studies have shown that overexpression of α-synuclein inhibits the release of catecholamines from adrenal chromaffin and PC12 cells, probably owing to a reduced pool of readily releasable vesicles (9).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, this deficit was localized to the dopamine inputs to dorsal striatum. These findings are reminiscent of our previous work on α-and γ-synuclein double-knockout and α-, β-, γ-synuclein triple-knockout mice, in which we showed that synucleins negatively regulate dopamine release in the dorsal but not ventral striatum (16,20).…”
Section: Discussionsupporting
confidence: 87%
“…(B) Rotarod performance was impaired in 18-but not in 3-mo-old SNCA-OVX mice. Two-way ANOVA of square-root transformed data: main effect of age: F (1,28) = 25.95, ***P < 0.001; main effect of genotype: F (2,27) = 3.49, *P < 0.05; genotype/age interaction: F (2,27) = 6.14, **P < 0.01; separate ANOVAs revealed no main effect of genotype at 3 mo (F < 1, P > 0.05), but a significant main effect of genotype at 18 mo (F (2,15) = 10.04, **P < 0.01) (Tukey post hoc test *P < 0.05, **P < 0.01), n = 3-8), which remained significant when body weight was included as a covariate (ANCOVA: main effect of genotype: F ( results are consistent with previous finding that striatal SNARE complex formation in striatum is not regulated by synucleins (16). We next explored the alternative hypothesis that α-syn might restrict dopamine release by altering the distribution of the vesicular pool in dopamine axons in the dorsal striatum (17).…”
Section: No Change In Snare Complex Formation But Changes In Dopaminesupporting
confidence: 90%
“…Studies in mice with knockout of a-, b-and g-synuclein (triple knockout mice) so far show an increase in synaptic transmission only in young (3-months-old) but not in adult mice [43]. However, a more recent study demonstrated an increase in dopamine release in 1 year old triple knockout mice [44], which again argues for a negative regulatory function of a-synuclein in exocytosis ( Table 2).…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 99%